Canva-Based Educational Game “Unlock Your Potential”: Developing Arabic Learning Media for Grade X - Tania, Tania; Ammar, Farikh Marzuki (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
Technological advances in education can be a means to develop digital-based interactive learning media. Innovative media is considered capable of presenting a more meaningful learning atmosphere. In learning Arabic, students often complain of difficulties and get bored with learning that is considered monotonous. This encouraged researchers to then develop a product in the form of an educational game based on the Canva application as an alternative Arabic learning media. Through this product, it is hoped that students will be able to be motivated in learning Arabic. This research uses the RnD research type with the Hannafin and Peck development model. The media development product trial was carried out at SMA Muhammadiyah 2 Sidoarjo by taking a sample of 8 class X students. The data collection instruments in the form of questionnaires include expert team validation test sheets and student response sheets. Based on the results of the validation test from the expert team, the product developed can be categorized as “very valid”, as well as the responses of students in the trials that have been carried out show a fairly high interest in the media, thus indicating that the product development of educational game media based on Canva is very valid and includes feasible to be implemented in Arabic language learning in class X.